Evaluation of a home pharmaceutical care service model for home-based patients receiving anticoagulation therapy within county-level medical community - JianAo Song; Bin Chen; Jinhui Sun; KaiZhan Zhuang (PLoS ONE, 2026)
Objective To establish a systematic, standardized, and operational model of home pharmaceutical care for patients with anticoagulant treatment in county-level medical community. Methods A home pharmaceutical care service team was constituted by pharmacists and physicians from the county-level medical community. A home-based pharmaceutical care survey was conducted for patients with long-term oral anticoagulants (VKAs, rivaroxaban, dabigatran and apixaban). The patients’ awareness and adherence score to oral anticoagulants(OATs) was evaluated before and after home pharmaceutical care service. The awareness and adherence score were evaluated with awareness questionnaires and Morisky Medication Adherence Scale-8 (MMAS-8), respectively. The paired-sample t tests were used to compare the awareness and adherence score. Results Finally, totally 95 patients completed the survey. Among these patients, 29 patients were in the VKAs group and 66 patients were in the NOACs group. Following the implementation of home pharmaceutical care service, there was an increase in the awareness score, rising from 5.02 ± 1.71 to 8.09 ± 1.25 ( p < 0.001). Similarly, the adherence score increased from 4.66 ± 1.66 to 6.94 ± 0.59 ( p < 0.001). Conclusions This pilot study demonstrates that the home pharmaceutical care service model implemented within county-level medical community for anticoagulation treatment is feasible and shows promise in improving anticoagulation knowledge and medication adherence among patients.The findings provide preliminary evidence for a service model that could be further evaluated. Future controlled studies are warranted to confirm its efficacy and to investigate its impact on clinical health outcomes.